Kesetaraan Laki-Laki dan Perempuan dalam Perspektif Tafsir Tarbawi QS. At-Taubah Ayat 71 terhadap Tantangan di Era Modern - Dinanti Rusti, Dinda; Jamilah Sari, Nur; Puspika Sari, Herlini (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study examines the concept of gender equality in Islam through the perspective of tafsir tarbawi by focusing on the interpretation of QS. At-Taubah verse 71. The research aims to explore the meaning of equality between men and women and its relevance to the challenges of gender issues in the modern era. Using a qualitative research design with a library research approach, this study analyzes classical and contemporary tafsir sources, Islamic education books, and scholarly articles. The data were collected through systematic literature review and analyzed descriptively and analytically to identify key educational and moral values within the verse. The findings reveal that Islam upholds equality between men and women in spiritual, moral, and social responsibilities, as reflected in the tafsir of Ibn Kathir, Al-Qurthubi, and Al-Muyassar. However, in modern society, patriarchal culture, gender stereotypes, and structural discrimination still hinder women’s leadership and participation in public life. These challenges illustrate that gender equality remains an ongoing struggle despite increased awareness and education. The study implies that tafsir tarbawi provides a constructive framework for integrating Islamic values of justice and cooperation into education and social institutions. It contributes to advancing inclusive and contextual Islamic education paradigms that promote mutual respect and equal opportunity.